Attention and Reaction Time in Shotokan Athletes (Revista de Artes Marciales Asiáticas, 2012)
The aim of this study is to analyze the attention capacity and the reaction time in Portuguese karate Shotokan athletes. Participated 96 Shotokan athletes from the Portuguese Karate Association. We physically characterized the sample (weight, height, body mass index, and body fat mass percentage) and evaluated Simple Reaction Time (TRS), Choice Reaction Time (TRE), Decision Time (TD) and the Distributed Attention (AD). Data was analyzed according to athletes’ group age (15 to 19 yr, 20 to 35 yr and more than 35 yr), level of graduation (9th to 4th kyu, 3rd to 1st kyu, DAN) and by gender (male and female). Male athletes present significant differences from female athletes in height, weight, years of practice and body fat mass. In relation to TRS all groups tend to a value near to 300 ms without significant differences among them, but the TRE and the TD are significantly higher in the Dan athletes and in the +35 yrs athletes than in the other groups. On the other hand the Dan and +35 yrs athletes tend to do less mistakes. Gender does not influence significantly the reaction time in the Shotokan karate athletes, but it seems that women tend to have smaller reaction times than men. Athletes with more years of practice and more graduation need more time to reply to the stimulus than the other athletes, but they tend to do fewer mistakes on their choices than other subjects. As for distributed attention, no significant differences were found in function of the athlete graduation, nor in function of gender. However, for distributed attention, we found statistical significant differences in function of the age, with the oldest athletes presenting lower levels of distributed attention. Our results seem to show that is necessary to do some modifications in the training process of Portuguese Shotokan karate athletes.